P24 Presence of impaired baroreceptor sensitivity is a poor prognostic marker in cirrhosis. (6th September 2011) - Rye, K; Mortimore, G; Austin, A; Freeman, J
Abstract : Introduction: Autonomic function is essential for blood pressure control and baroreceptor sensitivity (BRS) acts as a composite marker of overall function. Both sympathetic and parasympathetic function is impaired in cirrhosis. Impaired BRS predicts death in cardiovascular diseases and chronic kidney disease. Aim: The aim of the present study was to assess the relationship between BRS and liver disease severity, systemic and portal haemodynamics and mortality in cirrhosis. Method: Prospective study of 29 cirrhotic patients. Systemic haemodynamics and BRS were assessed non-invasively using the Finometer. ® Spontaneous BRS was calculated from the regression of pulse interval on systolic blood pressure. Portal pressure was assessed by measurement of the hepatic venous pressure gradient (HVPG). Gastroscopy assessed variceal size and 1-year probability of bleeding according to the NIEC index. Results: 20 male (69%), median age 47 years (42–55), Child-Pugh score 6 (Class A 18, B 10, C 1) and MELD 10 (8–13). BRS was impaired in cirrhosis (median 4.2 ms/mm Hg, IQR 2.5–6.2 ms/mm Hg) but was not related to Child-Pugh score or MELD. Significant differences in BRS were seen with respect to gender (Female 2.0 ms/mm Hg vs male 5.8 ms/mm Hg, p=0.0125), presence of varices (present 3.8 ms/mm Hg vs absent 8.3 ms/mm Hg, p=0.0206), and ascites (ascites 2.0 ms/mm Hg vs no ascites 5.3 ms/mm Hg, p=0.0433). No significant differences in BRS were seen according to alcohol intake. A significant negative correlation was seen between BRS and age (r=−0.46, p=0.0130), heart rate (r=−0.56, p=0.0015), HVPG (r=−0.69, p<0.0001) and 1-year probability of variceal bleeding (r=−0.43, p=0.0199). Over a median follow-up of 710 days, 8/29 (27.6%) patients died with median time to death 854 days. Mortality was significantly higher in patients with HVPG greater than or equal to 10 mm Hg than without clinically significant portal hypertension (p=0.0024) and with a MELD score greater than or equal to 17 (p<0.0001). When stratified according to BRS (less than, or greater than or equal to 6 ms/mm Hg), mortality was significantly higher in patients with more severe impairment (<6 ms/mm Hg) than with preserved BRS (33% vs 12.5%, p=0.0034) despite no significant difference in Child-Pugh score, MELD, systemic haemodynamics, HVPG or length of follow-up. Patients with impaired BRS had significantly higher probability of variceal bleeding, and were more likely to have ascites (24% vs 0%). Conclusion: BRS is not related to liver disease severity as assessed by Child-Pugh or MELD but a significant inverse correlation exists between BRS and HVPG. Compared to patients with preserved BRS, patients with significant impairment of BRS have a higher mortality, a higher probability of variceal bleeding and are more likely to have ascites. Impairment of BRS appears to be a poor prognostic factor independent of liver disease severity or portal pressure, possibly relating to a failure to respond to the haemodynamic challenges associated with complications in cirrhosis.